1990
DOI: 10.1093/clinchem/36.8.1483
|View full text |Cite
|
Sign up to set email alerts
|

Preanalytical increase of ammonia in blood specimens from healthy subjects

Abstract: The course and magnitude of spontaneous increase in ammonia concentration in plasma on standing were investigated with EDTA-treated blood specimens from 36 healthy subjects with use of a sensitive and precise enzymic method. Over 90 min, the rates of increase were virtually constant at fixed temperature. The mean (and SE) rates at 0, 20, and 37 degrees C were 3.9 (0.23), 5.2 (0.23), and 25.2 (0.59) mumol/L per hour, respectively. At these temperatures, the plasma contributed at most 7%, 15%, and 10%, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(35 citation statements)
references
References 5 publications
2
31
0
2
Order By: Relevance
“…The rates of increase estimated in these studies ranged from only 2-4 µmol/L per hour at 0-4 o C, and 5-6 µmol/L per hour at 20-22 o C, although confidence limits on these rates of increase were not given. 4,6 In our study, we observed no statistically significant difference in plasma ammonia concentrations after heparinized whole blood was held for 5, 15, or 30 minutes either "on ice" or at room temperature. These findings were not unexpected, after extrapolating the published hourly rates of increase in ammonia concentration back to the time points that we examined, and given the published analytical standard deviations for current methods for measuring ammonia.…”
Section: Discussionmentioning
confidence: 41%
See 4 more Smart Citations
“…The rates of increase estimated in these studies ranged from only 2-4 µmol/L per hour at 0-4 o C, and 5-6 µmol/L per hour at 20-22 o C, although confidence limits on these rates of increase were not given. 4,6 In our study, we observed no statistically significant difference in plasma ammonia concentrations after heparinized whole blood was held for 5, 15, or 30 minutes either "on ice" or at room temperature. These findings were not unexpected, after extrapolating the published hourly rates of increase in ammonia concentration back to the time points that we examined, and given the published analytical standard deviations for current methods for measuring ammonia.…”
Section: Discussionmentioning
confidence: 41%
“…These findings were not unexpected, after extrapolating the published hourly rates of increase in ammonia concentration back to the time points that we examined, and given the published analytical standard deviations for current methods for measuring ammonia. 4,6,11 In a recent retrospective study, Hashim and Cuthbert examined the plasma ammonia results for over 1,800 patients, where samples were collected in EDTA and transported on ice. They found no significant relationship between ammonia levels and pre-analytical time up to 30 minutes, and concluded that ammonia results are reliable if the total time that elapses from collection to result is <120 minutes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations